Prevalence and Type Distribution of Human Papilloma Virus (HPV) in Oral, Oropharyngeal, Cervical, and Vulvovaginal Cancers (Journal of Analytical Oncology, 2025)
Background: Human papillomavirus (HPV) is a major etiological agent in cervical cancer and is increasingly recognized as a driver of other anogenital and head and neck squamous cell carcinomas (HNSCCs). The oncogenic potential of HPV is primarily mediated by high-risk genotypes such as HPV16, HPV18, HPV31, and HPV45, whose E6 and E7 oncoproteins disrupt p53 and retinoblastoma pathways. While the burden of HPV-associated cervical cancer is well documented, data on the prevalence and genotype distribution of HPV in oral, oropharyngeal, vulvar, and vaginal cancers in India remain limited.Objective: To identify the disease burden and determine the prevalence and genotype distribution of high-risk HPV (16, 18, 31, 45) in biopsy-proven squamous cell carcinomas of the cervix, oral cavity, oropharynx, vulva, and vagina.Methods: We conducted a retrospective analysis of 131 patients with squamous cell carcinomas diagnosed between September 2022 and August 2024 at Vydehi Institute of Medical Sciences and Research Centre, Bangalore, India. PCR-based HPV detection was employed to determine the presence of high-risk HPV types 16, 18, 31, and 45 targeting the E6/E7 regions of high-risk HPV. Clinical and pathological data, including tumor stage and demographic variables, were analyzed.Results: Overall HPV prevalence was 90.1%. Site-specific positivity was highest in cervical cancers (95.8%) and vulvovaginal cancers (100%), followed by oral (84.2%) and oropharyngeal (66.7%) cancers. HPV16 and HPV31 were the dominant genotypes across all tumor sites, whereas HPV18 and HPV45 were detected at lower frequencies. Cervical cancer cases predominantly presented in advanced stages (FIGO IIB–IIIB), while vulvovaginal cancers were diagnosed at earlier stages.Conclusion: HPV infection, particularly with HPV16/31, is highly prevalent in multiple anogenital and head and neck squamous cell carcinomas in this Indian cohort. These findings reinforce the importance of HPV vaccination programs, highlight the need for comprehensive HPV screening strategies, and suggest that P16 immunohistochemistry (IHC) should be integrated with PCR-based detection to establish oncogenic causality.